The Relationship Between Teacher's Communication Skills and Students’ Learning Interest in the Fourth-Grade Social Science Learning Subject in Elementary School - Eirene Sirait; Bogor Lumbanraja; Patri Janson Silaban; Dewi Anzelina; Anton Sitepu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the relationship between teacher communication skills and students’ learning interest in social science learning subjects. The research was conducted in class IV at SD Negeri Medan Johor. Researchers used associative quantitative research methods. The population used was 36 students at class IV SD Negeri 060938 Medan Johor. Sampling used saturated sampling. The research results indicate that the results obtained from the correlation test can be seen in the correlation coefficient, rcount 0.946 ≥ rtable 0.329. Hence, it can be concluded that the alternative hypothesis (Ha) is accepted where there is a significant relationship between communication skills and students' learning interests at SD Negeri 060938 Medan Johor. In addition, it can be seen from the results of the t-test where tcount 17.052 ≥ ttable 2.030, hence the hypothesis (Ha) is accepted. It shows that there is a positive significant relationship between teacher communication skills and students’ learning interests in social science learning subjects in class IV at SD Negeri Medan Johor in the academic year 2022/2023.